Short-patch correction of C/C mismatches in human cells - Muheim-Lenz, Regula; et al. (Nucleic Acids Research, 2004)
We examined whether the human nucleotide excision repair complex, which is specialized on the removal of bulky DNA adducts, also displays a correcting activity on base mismatches. The cytosine/cytosine (C/C) lesion was used as a model substrate to monitor the correction of base mismatches in human cells. Fibroblasts with different repair capabilities were transfected with shuttle vectors that contain a site-directed C/C mismatch in the replication origin, accompanied by an additional C/C mismatch in one of the flanking sequences that are not essential for replication. Analysis of the vector progeny obtained from these doubly modified substrates revealed that C/C mismatches were eliminated before DNA synthesis not only in the repair-proficient background, but also when the target cells carried a genetic defect in long-patch mismatch repair, in nucleotide excision repair, or when both pathways were deleted. Furthermore, cells deficient for long-patch mismatch repair as well as a cell line that combines mismatch and nucleotide excision repair defects were able to correct multiple C/C mispairs, placed at distances of 21-44 nt, in an independent manner, such that the removal of each lesion led to individual repair patches. These results support the existence of a concurrent short-patch mechanism that rectifies C/C mismatches.